Dairy-form as an index to character - Owens, George Washington (My University, 1899)
Introduction: The growing importance of the dairy industry in Kansas during the past few years, has attracted much attention to this new line of business in our state. This interest is manifested in the numerous, animated, discussions, which take place through the leading agricultural and stock journals, upon almost every phase relative to the dairy business. With the increase of the demand for dairy products, there comes an increased effort on the part of the producers to supply this demand. And this constant aim at improvement and competition has suggested and developed many useful, economical appliances and methods which have contributed to, and acted as a stimulus for the success of the dairy industry in the West. Along this line, we find improved methods of feeding, based on scientific principles, in which, by making use of our knowledge of chemistry of foods, and the comparative nutritive ratio of different foods, we have determined on the method of balanced rations. Of these we will say more presently. While methods of care and feeding are of great importance, there are other factors which exercise a great influence, upon the dairy returns. Paramount among these factors is that of object in breeding. Great attention has been paid of late years to the breeding of cattle for dairy purposes. In most cases, kit has been customary to designate some particular breed as a dairy breed, and another as a beef breed, irrespective of certain peculiar type and individual qualities, any contemplated or proposed improvement in the dairy business or herd, was always to be made within or of some particular breed.
Citation: Owens, George Washington. Dairy-form as an index to character. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: New Appliances; Purpose in Breeding; Theses; Manuscripts (documents)